Intravenous pharmacokinetics of moxifloxacin following simultaneous administration with flunixin meglumine or diclofenac in sheep - Altan, Feray; Corum, Orhan; Yildiz, Ramazan; Eser Faki, Hatice; Ider, Merve; Ok, Mahmut; Uney, Kamil (Wiley, 2020)
AbstractIn this study, the pharmacokinetics of moxifloxacin (5 mg/kg) was determined following a single intravenous administration of moxifloxacin alone and co‐administration with diclofenac (2.5 mg/kg) or flunixin meglumine (2.2 mg/kg) in sheep. Six healthy Akkaraman sheep (2 ± 0.3 years and 53.5 ± 5 kg of body weight) were used. A longitudinal design with a 15‐day washout period was used in three periods. In the first period, moxifloxacin was administered by an intravenous (IV) injection. In the second and third periods, moxifloxacin was co‐administered with IV administration of diclofenac and flunixin meglumine, respectively. The plasma concentration of moxifloxacin was assayed by high‐performance liquid chromatography. The pharmacokinetic parameters were calculated using a two‐compartment open pharmacokinetic model. Following IV administration of moxifloxacin alone, the mean elimination half‐life (t1/2β), total body clearance (ClT), volume of distribution at steady state (Vdss) and area under the curve (AUC) of moxifloxacin were 2.27 hr, 0.56 L h−1 kg−1, 1.66 L/kg and 8.91 hr*µg/ml, respectively. While diclofenac and flunixin meglumine significantly increased the t1/2β and AUC of moxifloxacin, they significantly reduced the ClT and Vdss. These results suggest that anti‐inflammatory drugs could increase the therapeutic efficacy of moxifloxacin by altering its pharmacokinetics.
Keywords: sheep; Diclofenac; Sheep; Anti-Inflammatory Agents, Non-Steroidal; Moxifloxacin; Reproducibility of Results; Flunixin Meglumine; Anti-Bacterial Agents; Clonixin; diclofenac; flunixin meglumine; Animals; Pharmacokinetics; Administration, Intravenous; Female; Longitudinal Studies; moxifloxacin; pharmacokinetics; Chromatography, High Pressure Liquid; 3. Good health